A review of studies on counselor qualification - Ancheta, Milagros Fe 1928- (1969)
Centered on the subject of factors that make an effective counselor, the study aims to survey findings of research studies and literature written pertinent to counselor qualifications. The study will be beneficial to counselors who are seeking to establish a clearer professional identity, as well as to school administrators and classroom teachers who are seeking to utilize more effectively the competencies of school counselors.
Seminar paper.
Keywords: Student counselors -- Philippines; Counselors -- Philippines